Relationship Relationship between Knowledge and Attitude of Mothers About Nutrition with Stunting Prevention at Disaster Survivors' shelters in the Palu and Sigi District : Knowledge and Attitude of Mothers About Nutrition with Stunting Prevention at Disaster Survivors' shelters in the Palu and Sigi District - Supirno, Supirno (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2021)
ABSTRACT Central of Sulawesi is one of the provinces that is prone to disasters, the disaster problems in 2018 have not been completely resolved, while the stunting problem also still needs prevention efforts, both in Palu City and Sigi Regency. The purpose of the study: to analyze the relationship between mother's knowledge and attitudes with efforts to prevent stunting in Palu and Sigi shelters post disasters. The research method uses a cross sectional design, the population is mothers who have toddlers in permanent housing after the disaster, the sample is taken by cluster sampling as many as 100 people. Data were collected using questionnaires and analyzed univariately and bivariately with the help of a computer program. The results of the study were mostly knowledge about nutrition in the poor category, the attitude of the mother was mostly negative and from the results of bivariate analysis with the chi square test there was a relationship between maternal knowledge about nutrition and stunting prevention efforts (p = 0.026). There is a statistically significant relationship between the mother's attitude (p.0.000). Conclusion: knowledge about malnutrition and attitudes are mostly negative. There is a significant relationship between knowledge and attitudes of mothers with stunting prevention efforts in permanent housing after disaster at Tondo Palu city and Pombwewe, Sigi Regency. Keywords : Knowledge, attitude, stunting prevention